FRAMING GM CROPS AS A SOLUTION FOR GLOBAL FOOD SECURITY - Reddy, P.B (International Journal of Research -GRANTHAALAYAH, 2015)
Genetically Modified organisms (GMOs) are a tool of solution in helping to tackle the challenge of global food security for ever growing population. With global population expected to grow by 40% in the next few decades, agriculture will need to become more productive and more sustainable in order to keep pace with rapidly increasing demands. The current biotechnology permits to alter the genetic makeup of living organisms to produce much quicker and beneficial results. The present study is aimed to evaluate the economic, environmental and nutritive benefits of transgenic crops. We have reviewed many articles from various journals, blogs and media clips related to the subject. Results indicate that the use of GMOs have many potential benefits that include increased crop production, improved nutrition, and drought tolerance, reduced fertilizers and pesticides, better environmental condition, improved economic benefits and improvement in fruit storage. Conversely, there are few concerns about possible unpredicted adverse health effects, environmental damage, gene pollution and business exploitation. Results also indicate the towering costs and uncertainty about the guidelines of GMOs have slowed the rate of innovation of new qualities and prevented set ups and major corporate sectors from developing many second-generation varieties to facilitate the improvement of our well-being.